Hadronic deuteron polarizability contribution the hyperfine structure in muonic deuterium - Eskin A.V.; Martynenko A.P.; Elekina E.N. (EPJ Web of Conferences, 2017)
The calculation of the contribution to the polarizability of the nucleus to hyperfine structure of muonic hydrogen is carried out within the unitary isobar model and on the basis of experimental data on the structure functions of deep inelastic lepton-proton and lepton-deuteron scattering. The calculation of virtual absorption cross sections of transversely and longitudinally polarized photons by nucleons in the resonance region is performed in the framework of the program MAID.